Development of a Real-Time Air Quality Monitoring System Using IoT and Data Analytics - Ahmed Boukhalfa; Mohammed Benslimane; Lynda Ghemri (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This paper introduces a real-time air quality monitoring system based on the Internet of Things (IoT) integrated with advanced data analytics. The system uses low-cost sensors to gather data on air pollutants, which are then processed using cloud computing and visualized through a web application. Field tests conducted in urban and suburban areas demonstrate the system’s effectiveness in providing accurate, real-time air quality information, enabling timely responses to pollution events.